Uma Etnografia Sem Órgãos: Corpos Em Ato No Teat(R)O Oficina - Azevedo, Ruan Felipe De [UNIFESP] (2018)
The Ethnography That Gives Substance To This Dissertation Is Based On Rehearsals Of The Spectacle Bacchantes, Staged By Teat(R)O Oficina, Between The Years Of 2016 And 2017. During This Period, I Focused By Attention On The Ways In Which The Bodies Are Constructed By Relations Of Various Orders. In The Theatrical Company Teat(R)O Oficina, The Actors" Bodies, The Public And Even This Anthropologist Are Sometimes Captured By A Turn. In Its Performativity, This Turn Implies Openness To Relations With Heterogeneous Beings Of Different Cosmos. Such Relations, Knowledge And Performances Are Not Made By Means Of The Representations Of The World, But By Means Of Transformational Agency And Transformational Effects. Beyond The Actors, Such Relations Mobilize A Cosmopolitic That Involves The Theater Building, The Territory Around, The Rivers, The Residents And Other Visible And Invisible In/Who Inhabt Beings The City.